KAJIAN LEPTOSPIROSIS PADA SAPI POTONG DI DAERAH ALIRAN SUNGAI PROGO DAERAH ISTIMEWA YOGYAKARTA (The Study of Bovine Leptospirosis in Progo Watershed, Yogyakarta) - Mulyani, Guntari Titik; Sumiarto, Bambang; Artama, Wayan Tunas; Hartati, Sri; J, Juwari; S, Sugiwinarsih; Putra, Henricus Roby Cahya; Widodo, Estu (Universitas Syiah Kuala, 2016)
The purpose of this study was to determine the prevalence, serovar, and risk factors of leptospirosis on cattle in Progo watershed. A total of 330 cattle samples were clinically examined and blood was collected for Leptospira examination using microscopic agglutination test (MAT). Results of MAT were used as dependent variable (Y), while breeders, cattle, shed, and feed factors were used as the independent variable (X). Univariate analysis, bivariate analysis with chi square, odds ratio, and multivariate with logistic regression were implemented to analyze the data. The results showed that all cattle were cinically health, 13.03% (43/330) cattle were positively leptospirosis which 37 out of 193 (9.17%) cattle belongs to the farmer. Mostly, leptospirosis cases were caused by hardjo serovar (38.0%). Risk factors influencing the prevalence of leptospirosis were caused by some factors such as the presence of rats in cage (OR 2.7), the distance of waste disposal which should be less than approximately 5 meters (OR 2.1), feed concentrates, grass and rice straw (OR 0.4), grazing (OR 0.2), and concentrate feed and rice straw (OR 0.1). It can be concluded that leptospirosis infection on cattle in Progo watershed is 13.03% (at livestock level) and 19.17% (at farm levels). Factors of rat in the cage and the distance of waste disposal (5 m) increase the risk of leptospirosis cases. Factors of feed combine with concentrate and rice straw as well as grazing reduced the risk of leptospirosis in cattle, but the addition of grass in concentrate feed and rice straw provides a greater risk of leptospirosis infection compare to concentrate feed and rice straw alone.Key words: beef cattle, leptospirosis, prevalence, risk factors